Russia and the olympic movement : a study of Russian national identity as described in the newspaper Sovetskij Sport during the winter olympic games of 1988, 1992, 1994, and in the future winter olympic games of 2014 - Nikitin, Anna (2010)
The topic of the thesis deals with Russia and the Olympic Movement, studying Russian national identity as it is described in the newspaper Sovetskij Sport during three past Winter Olympic Games (1988, 1992, 1994) and the upcoming Winter Olympic Games that take place in Sochi 2014 in the framework of international politics. The research task is to analyze, what kinds of discourses do the writings of Russian Olympic Committee’s leading sports journal Sovetskij Sport use in times of the above mentioned Olympic Games in relation to the “West”. It is studied, in which way can these discourses be understood as representations of national identity in the framework of political upheavals.